DAYA KECAMBAH DAN PERTUMBUHAN Mucuna bracteata MELALUI PEMATAHAN DORMANSI DAN PEMBERIAN ZAT PENGATUR TUMBUH GIBERELIN (GA3)v - Hardianti Putri Sari; Chairan Hanum; Charloq Charloq (Jurnal Agroekoteknologi, 2014)
The generative propagation of Mucuna bracteata is very difficult and requires special treatment.Dormancy breaking in hard seed of Mucuna purpose to enhance germination. The research wasconducted at the public land, Tanjung Selamat, Deli Serdang from November 2012 to February2013, using a randomized block design with 2 factors and 3 replications. The first factor was thedormancy breaking (control, cutting the seed coat, polished with sand paper, and hot water soaking)and the second factor was gibberellin (GA3) (0, 150, 300 and 450 ppm). The parameters observedwere the germination, long tendrils, number of leaves, shoot dry weight, root dry weight. The resultshowed that the dormancy breaking significantly affected to all parameters. Giving of Gibberellins(GA3) significantly affected to the germination and shoot dry weight. Interaction between dormancybreaking and Gibberellins significantly affected to the germination and shoot dry weight. The bestgermination were showed by cutting the seed coat and giving 300 ppm GA3.Keywords : dormancy fracturing, gibberellins, germination, Mucuna bracteata.